2019
DOI: 10.5811/cpcem.2019.4.41305
|View full text |Cite
|
Sign up to set email alerts
|

An Unusual Presentation of Postpartum Spontaneous Coronary Artery Dissection

Abstract: The postpartum population is one with a unique physiologic profile that predisposes these patients to rare and often life-threatening conditions. Herein, we discuss a case of a 37-year-old, multiparous female who presented to the emergency department with vague chest discomfort 14 days after delivering her sixth child via vaginal delivery. The patient was found to have elevated cardiac biomarkers and was ultimately diagnosed with pregnancy-related spontaneous coronary artery dissection (P-SCAD). This case repo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(12 citation statements)
references
References 9 publications
1
11
0
Order By: Relevance
“…These assertions are supported by the findings yielded by a number of SCAD/pregnancy-focused studies, including Saw et al's 3 prospective multicenter SCAD review across Canada, where P-SCAD patients experiencing acute MI were found to be more likely to have fewer risk factors than NP-SCAD patients. 12 , 13 , 17 , 20 , 33 Because these results pertain to mostly Caucasian women, it is worth noting that they are corroborated by the findings yielded by Clare et al's 25 more ethnically diverse study. Thus, although race does not appear to influence the identification of P-SCAD, accurate representation of diverse populations in SCAD registries is warranted.…”
Section: Discussionsupporting
confidence: 68%
See 3 more Smart Citations
“…These assertions are supported by the findings yielded by a number of SCAD/pregnancy-focused studies, including Saw et al's 3 prospective multicenter SCAD review across Canada, where P-SCAD patients experiencing acute MI were found to be more likely to have fewer risk factors than NP-SCAD patients. 12 , 13 , 17 , 20 , 33 Because these results pertain to mostly Caucasian women, it is worth noting that they are corroborated by the findings yielded by Clare et al's 25 more ethnically diverse study. Thus, although race does not appear to influence the identification of P-SCAD, accurate representation of diverse populations in SCAD registries is warranted.…”
Section: Discussionsupporting
confidence: 68%
“… 35 The authors challenge the prevalent view that hormones (such as contraceptives and hormone replacement therapy) and changes in hormone levels during birth are risk factors for SCAD because SCAD incidence is low compared with the widespread application of those hormones. Likewise , Saw et al 37 and Alterie et al 33 posit that other stressors and arteriopathies can contribute to the emergence of SCAD, given that psychological and physical precipitating stressors have been identified as risk factors. 11 …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…42,43 Implementation of postpartum clinics or home visits did not tend to have an effect, [44][45][46] although women at risk for depression who self-excluded from home visits were more likely to visit an ED. 47 Of the 108 case reports (►Supplementary Table S1, available in the online version), 37% dealt with cardiovascular disease, including aortic dissection, 48 peripartum cardiomyopathy, 15,[49][50][51][52][53][54][55][56] spontaneous coronary artery dissection, 48,[57][58][59][60][61][62][63][64][65][66][67][68] and ST-elevation myocardial infarction. 62,63,[69][70][71] The cardiovascular category also had the highest number of cases that were associated with maternal mortality (n ¼ 3).…”
Section: D-dimers and Clinical Decision Rules To Address The Likeliho...mentioning
confidence: 99%